Characterization of Endogenous Transglutaminase Enzyme of Yellow Pike Conger’s Liver (Congresox talabon) - Santhy Wisuda Sidauruk; Tati Nurhayati; Untung Trimo Laksono (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Transglutaminases have been found in various living organism, such as mammals, plants,microorganisms, and marine organisms including fishes. Transglutaminases have many various functionssuch as food or non-food application and in pharmaceticals industries. This research was aimed tocharacterize transglutaminase that obtained from fisheries byproducts such as catadromous fish the yellowpike conger’s liver.. The yield of yellow pike conger’s liver was 0.88±0.11%. Crude transglutaminase from liverof yellow pike conger had specific activity of 1.375 U/mg with optimum pH at 7.5 and optimum temperatureat 50°C. The activity of transglutaminase were increased on Mg2+ ion dependent. Crude transglutaminasehad molecular weight of 27.48; 37.00; 69.51; 78.89; 88.18; 108.45; 134.10; and 172.12 kDa.